Psychotherapeutic interventions for depressive symptoms in older adults in a community setting: a systematic review protocol - Morgado, Bruno; Silva, Celso; Agostinho, Inês; Brás, Filipe; Amaro, Pedro; Lusquinhos, Leonel; Schneider, Brooke C.; Fonseca, Cesar; Albacar-Riobóo, Núria; Pinho, Lara (Frontiers in Psychiatry, 2024)
Depression is a prevalent illness among the elderly, so psychotherapeutic interventions new nonpharmacological interventions are needed to promote health and quality of life. This literature review aims to identify trials of any psychotherapeutic interventions aimed at reducing depressive symptoms in older adults. This literature review aims to identify trials on any psychotherapeutic interventions that effectively reduce depressive symptoms in older adults.This literature review aims to carry out trials on any psychotherapeutic interventions that reduce depressive symptoms in older adults. A systematic literature review with a meta-analysis will be carried out. The following databases will be searched: CINAHL Plus with Full Text, MedicLatina, MEDLINE with Full Text, and Psychology and Behavioral Sciences Collection. To minimize bias, four reviewers will independently assess the inclusion of studies. The fifth reviewer will be responsible for disaggregating inclusion and exclusion between two authors.The results of the analysis will be grouped in a table with the characteristics of the included studies, including author, year, sample, objectives, methods, assessment instruments, psychotherapeutic interventions, results, follow-up and a data compilation scheme. This scientific article is a systematic review protocol for which the data has already been extracted and is being analyzed.Examples of possible strategies to include cognitive restructuring and mental health programs for older adults in community settings. With this clear and direct identification of psychotherapeutic interventions, it will be clearer for mental health professionals to be able to intervene effectively to promote the mental health and well-being of older adults.